The Effect of Fasting Time on The Growth Performance and Survival Rate of Carried Koi Fish (Cyprinus carpio) Rearing at Temperature Optimum - Tanjung, Andini Fadila; Putriningtias, Andika; Haser, Teuku Fadlon; Febri, Suri Purnama; Harahap, Antoni; Darsiani, Darsiani (Jurnal Ilmiah Samudra Akuatika, 2023)
Koi fish is a type of ornamental fish whose color and unique body shape are one of the attractions of koi fish. This study aims to determine and evaluate the effect of fasting time on the growth and survival of koi fish (Cyprinus carpio) which are fasted periodically at optimum temperature. The method used in this study was the RAL experimental method (completely randomized design) with 4 treatments and 3 replications. The fasting treatment used was the non-fasting treatment as (control), 1 day of fasting and 1 day of feeding, 1 day of fasting and 2 days of feeding, and 1 day of fasting and 3 days of feeding. Each treatment used seeds measuring 4-5 cm. Parameters observed were absolute weight growth, absolute length growth, daily growth rate, survival rate and feed conversion ratio. The results of the study based on the analysis of variance showed that fasting in koi fish had a significant effect (P<0.05) on absolute weight growth and daily growth rate and had no significant effect on growth in absolute length, survival raet and feed conversion ratio. The best treatment of periodic fasting is in treatment P2 = 1 day of fasting 1 day of being feed.